A Study on the Sovereign Debt Crisis in Europe - Fathi, Abdulkarim Osman (2014)
This study talks about the financial crisis in Europe, it also goes around the effect that it had on these countries’ economies and how much they got hurt. As the study says most of the European countries used issuing debts with high interest rates to fund their financial and monetary needs for expansions that was not well compensated with projected income, which eventually made them realize that they unable to service even the interest part of it, then restructuring, requesting for bails and other methods were taken as steps in solving the problem. The primary research methodology used in this dissertation involves the use of a combination of investigator triangulation which involves research results and statistical analysis using PIGS countries as a sample since they are the most effected economies. We also defined what Euro zone means and how is it formed beside the responsibility of those countries towards each other. Then we took the PIGS nations separately to analyze the actual cause of their own issues and why are they highly effected, beside we illustrated in this paper the social life of European and what do they think or know about the crisis and how much they should get involved to help overcoming the difficulties. This research talked about the banking sectors and their main contribution to the crisis, as they are one the biggest sectors that got involved and effected by large, so they had to comply with certain rules and procedures in order to be bailed out and overcome these issues. At the end there are several recommendations that we have suggested and concluded the report with.